P194 Once-Daily QVA149 Provides Superior Bronchodilation and Improves Lung Function Versus Twice-Daily Fluticasone/Salmeterol in COPD Patients: The ILLUMINATE Study. (19th November 2012) - Vogelmeier, C; Bateman, E; Pallante, J; Bryant, H; Alagappan, V; D'Andrea, P; He, E; Banerji, D
Abstract : Introduction: QVA149 is a novel inhaled once-daily dual bronchodilator containing a fixed-dose combination of the long-acting β2 -agonist (LABA) indacaterol and the long-acting muscarinic antagonist (LAMA) glycopyrronium, in development for the maintenance treatment of COPD. This study evaluated the superiority of QVA149 once daily in terms of efficacy over fluticasone/salmeterol twice daily in patients with COPD. Methods: In this 26 week, multicentre, double-blind, double-dummy, parallel-group study patients aged ≥40 years with moderate-to-severe COPD (post-bronchodilator FEV1/FVC <0.7 and FEV1 ≥40% to <80% predicted), no history of exacerbations in the previous year and smoking history ≥10 pack-years, were randomised (1:1) to receive QVA149 110/50µg (via the Breezhaler® device) or fluticasone/salmeterol 500/50µg (via the Accuhaler® device). The primary efficacy end point was standardised FEV1 area under the curve (FEV1 AUC0–12h) at Week 26. The pre-dose trough FEV1 on Week 12 and 26 and peak FEV1 on Day 1, Week 12 and Week 26 were also measured. Results: A total of 523 patients (35.1% on inhaled corticosteroids use) were randomised [QVA149, n=259; fluticasone/salmeterol, n=264; male (70.9%); mean age: 63.3 years; mean post-bronchodilator FEV1: 60.2% predicted], 82.6% completed. FEV1 AUC0–12h was found clinically meaningful and statistically significant in favour of QVA149 compared to fluticasone/salmeterol on Day 1, Week 12 and Week 26 (Least squares mean [LSM] treatment difference=70mL, 120mL, 140mL, respectively; all p<0.001). Pre-dose trough FEV1 was significantly (p<0.001) higher for QVA149 compared with fluticasone/salmeterol at Week 12 and 26 (LSM treatment difference=90mL and 100mL, respectively; p<0.001). The LSM treatment difference for peak FEV1 was also statistically significant for QVA149 compared with fluticasone/salmeterol on Day 1 (70mL), Week 12 (150mL) and Week 26 (150mL), all p<0.001. Conclusion: QVA149 once daily provided superior bronchodilation at all time-points compared to fluticasone/salmeterol twice daily and showed clinically meaningful improvements in lung function for a sustained period of 26 weeks. In moderate-to-severe COPD patients without a history of exacerbations in the previous year, LABA/LAMA dual bronchodilation with once-daily QVA149 proves a superior alternative to twice-daily fluticasone/salmeterol. Prof Claus Vogelmeier has served on scientific advisory boards for AstraZeneca, Boehringer Ingelheim, Chiesi, GlaxoSmithKline, Janssen, Novartis, Pfizer, Almirall, Takeda, and Sterna Biologicals; has been paid lecture fees by AstraZeneca, Chiesi, GlaxoSmithKline, Janssen, Talecris, Novartis, Boehringer Ingelheim, Takeda, and Pfizer. Prof Eric Bateman has served on advisory boards for Boehringer Ingelheim, AstraZeneca, Elevation Pharma, Napp Pharma, Novartis, Almirall, Forest, and Merck and Takeda; has served as a consultant to Navigant Consulting, IMS consulting group, ALK-Abello, Almirall, Hoffman la Roche, and ICON; has been paid lecture fees by AstraZeneca, ALK-Abello, Chiesi, Boehringer Ingelheim, GlaxoSmithKline, Nycomed/Takeda, Novartis, Pfizer, and Indegene Lifesciences Ltd.